Single-cell RNA-seq and pathological phenotype reveal the functional atlas and precise roles of Sox30 in testicular cell development and differentiation - Cheng-ting Xie; Hui-lian Zhang; Yi Li; Qian Li; Yi-xian Wen; Jin-yi Liu; Fei Han (Cell Death and Disease)
Abstract Sox30 has recently been demonstrated to be a key regulator of spermatogenesis. However, the precise roles of Sox30 in the testis remain largely unclear. Here, the specific functions of Sox30 in testicular cells were determined by single-cell sequencing and confirmed via pathological analyses. Sox30 loss appears to damage all testicular cells to different extents. Sox30 chiefly drives the differentiation of primary spermatocytes. Sox30 deficiency causes spermatocyte arrest at the early phase of meiosis I, with nearly no normally developing second spermatocytes and three new spermatocyte -subclusters emerging. In addition, Sox30 seems to play important roles in the mature phenotypes of Sertoli and Leydig cells, and the proliferation and differentiation of spermatogonia. The developmental trajectory of germ cells begins with spermatogonia and splits into two different spermatocyte branches, with Sox30-null spermatocytes and wild-type spermatocytes placed at divergent ends. An opposite developmental trajectory of spermatocyte subclusters is observed, followed by incomplete development of spermatid subclusters in Sox30-null mice. Sox30 deficiency clearly alters the intercellular cross-talk of major testicular cells and dysregulates the transcription factor networks primarily involved in cell proliferation and differentiation. Mechanistically, Sox30 appears to have similar terminal functions that are involved mainly in spermatogenic development and differentiation among major testicular cells, and Sox30 performs these similar crucial roles through preferential regulation of different signalling pathways. Our study describes the exact functions of Sox30 in testicular cell development and differentiation and highlights the primary roles of Sox30 in the early meiotic phase of germ cells.